The house: prepositions of place - Laiche Huaymana, Karen Jhoanna (2018)
This professional sufficiency exam that was supported through a learning session which is entitled "The House: Prepositions of place" and has as competencies: Understands everyday texts related to themselves, their family and their immediate environment. Produces different texts with cohesion and coherence, related to themselves and their family environment, using linguistic and non-linguistic elements. To achieve them, the following capacities have been considered: Predict the content of the text taking into account the paratextual elements. Identify the global or specific information of the text. Describe the information of a paratextual element using prepositions of place. Plan the production of the text, identifying the communicative situation. To measure achievement progress, the following indicators were formulated: Identifies the communicative situation by answering some questions and guessing the topic of the lesson. Identify vocabulary by looking at pictures and answering questions. Recognize the use of Prepositions of place describing an image. Produce a written text describing an image describing it with cohesion and coherence. The learning session has considered the didactic moments of beginning, process and exit. The theme of the session was contextualized with the parts of the house, objects that are in it, as well as the pet to motivate the learning of prepositions of place. For the evaluation, an observation sheet has been used with the proposed indicators, with a vigesimal evaluation scale from 0 to 20 and each indicator with a weight of 0-4. Metacognitive questions were also asked to reflect with the students on the process of learning during the session. Finally, at the end of the lesson the students managed to produce written texts of medium complexity describing the location of the objects that are in the house and they presented their products to the whole class for their improvement with the help of the teacher.